A Data Mining Approach for Prediction Modeling Using Association rule - Sarkhel H.Taher Karim; Rzgar Sirwan Raza (JOIV : International Journal on Informatics Visualization, 2019)
In the present work, a data mining approach is highlighted, a prediction optimization data mining approach association rule is chosen for performing prediction modeling in a supermarket application, a data mining prediction analysis model is formulated based on association rule is presented in this work.  The result of the model formulated is then compared with the result produced on the similar set of input on the traditional optimization problems. While comparing the results it was observed that the result produced by the presented model is much closer to the reality.